2004
DOI: 10.1161/01.atv.0000142806.59283.11
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low-Density Lipoproteins Stimulate Extracellular Matrix Metalloproteinase Inducer (EMMPRIN) Release by Coronary Smooth Muscle Cells

Abstract: Objective-Matrix metalloproteinases (MMPs) seem to play a prominent role in atherogenesis. Extracellular MMP inducer (EMMPRIN), a cell surface glycoprotein which stimulates MMP synthesis, has recently been detected in human atheroma. We have investigated the influence of oxidized low-density lipoproteins (oxLDLs) on EMMPRIN expression in human coronary artery smooth muscle cells (HCA-SMCs). Methods and Results-OxLDL induced a significant increase of EMMPRIN release into HCA-SMC supernatants and a concomitant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 25 publications
4
48
0
Order By: Relevance
“…EMMPRIN, a putative CyPA receptor, has been identified as a tumor cell membrane protein that is expressed in VSMC, is activated by ROS and stimulates matrix metalloproteinase production. 34 A recent study demonstrated ROS-dependent increases in EMMPRIN, 35 which may be activated by the binding of extracellular CyPA. 36 Therefore, ROS-induced secretion of CyPA may also contribute to the development of unstable atherosclerotic plaque and plaque rupture.…”
Section: Cypa and Atherosclerotic Unstable Plaquementioning
confidence: 99%
“…EMMPRIN, a putative CyPA receptor, has been identified as a tumor cell membrane protein that is expressed in VSMC, is activated by ROS and stimulates matrix metalloproteinase production. 34 A recent study demonstrated ROS-dependent increases in EMMPRIN, 35 which may be activated by the binding of extracellular CyPA. 36 Therefore, ROS-induced secretion of CyPA may also contribute to the development of unstable atherosclerotic plaque and plaque rupture.…”
Section: Cypa and Atherosclerotic Unstable Plaquementioning
confidence: 99%
“…Increased MMP expression was obtained following the exogenous treatment of fibroblasts with recombinant CD147 protein as well as the adenoviral transduction of fibroblasts with CD147 in the absence of tumor cells (Li et al 2001) These studies indicated that membrane bound and soluble CD147 are equally capable of inducing MMP production from fibroblast cells. The soluble form of CD147 has been detected in conditioned media as full length protein (Taylor et al 2002) or as part of shed microvesicles (Sidhu et al 2004), as well as in forms lacking the transmembrane and cytoplasmic domain derived from MMP mediated cleavage of CD147 from the cell surface (Haug et al 2004;Egawa et al 2006;Maatta et al 2006). …”
Section: Cd147 Function: An Inducer Of Matrix Metalloproteinasesmentioning
confidence: 99%
“…Increasing evidence shows that in response to certain proatherogenic stimuli such as oxLDL, EMMPRIN is upregulated strongly in atherosclerosis-related cells, including macrophages and coronary smooth muscle cells (Major et al, 2002;Haug et al, 2004;Schmidt et al, 2006). It also increases in activated platelets and mediated NF-jB activation by inducing the production of MMP-9, IL-6, and TNF-a (Schmidt et al, 2008).…”
mentioning
confidence: 99%